Clinical and Epidemiological Aspects of Basal Cell Carcinoma in Karachi (Medical Forum Monthly, 2024)
Objective: To study the clinical and epidemiological aspects of Basal Cell Carcinoma in Karachi and to compare this with western and local literature.Study Design: A descriptive study.Place and Duration of Study: This study was conducted at the Department of Pathology, PNS Shifa (Naval Hospital), Karachi from January 2012 to June 2015.Materials and Methods: All forty cases of Basal Cell Carcinoma diagnosed at PNS Shifa during the study period were included in the study. Skin biopsies were received at the Histopathology Laboratory. Age, gender, occupation, ethnic group, clinical presentation and history of any predisposing factors were recorded on a specially prepared proforma. Gross examination was performed; representative sections taken and tissues submitted for further processing. Microscopic examination was performed thereafter.Results: Elderly males were most commonly affected. Punjabis were the commonest ethnic group affected (42.5%). The commonest site was the face (72.3%). Two thirds of the patients had professions involving prolonged sun exposure. Most of the patients had solitary lesions (92.5%) with only three patients (7.5%) having multiple lesions. One patient had a positive family history of basal cell carcinoma (mother) and two patients had predisposing skin conditions.Conclusion: Basal Cell Carcinoma in Karachi is not uncommon. The findings of our study are in concurrence with local and western studies. However further studies need to be done to examine various clinical and epidemiological parameters in different parts of Pakistan.